Co-movements among the stock prices of new energy, high-technology and fossil fuel companies in China. (15th September 2017) - Zhang, Guofu; Du, Ziping
Abstract: In this paper, a three-variable TVP-SV-VAR model is developed and estimated to investigate the dynamic relationships among the stock prices of new energy, high-technology and fossil fuel companies. The results show that the stock prices of new energy companies correlate more highly with high-technology stock prices than with coal and oil stock prices. We also find empirical evidence of Chinese stock market turbulence in 2015 through our analyses of stochastic volatilities and dynamic correlations. Moreover, the impulse responses of all three of our variables to all three of the shocks have meaningful shapes, indicating that the Chinese government is faced with the double pressure of economic development and environmental protection. Highlights: A three-variable TVP-SV-VAR model is developed and estimated. This paper investigates the dynamic relationships among the NE, CO and HT indices. The CO index exhibits less volatility than the HT and NE indices. The results reveal the evidence of turbulence in China's stock market in 2015.